Strengthening Higher Agricultural Education in Africa - World Bank (World Bank, Washington, DC, 2020)
Over the last decade African governments’ and regional economic organizations have increasingly recognized the need to reshape higher agricultural education to meet the changing needs of the agri-food sector. There is a strong appetite for change but a need for a better understanding of the challenges that universities face in transforming into institutions that can be more dynamic and responsive, especially to the needs of the private sector, that is more relevant by the public sector and meet the rapidly growing demand for university places. The study is being prepared at a time when the World Bank along with other development partners are considering possible approaches to address these challenges. It follows regional dialogue on this theme in Africa in recent years involving African governments, regional agro-innovation and education networks including Regional Universities Forum for Capacity Building in Agriculture (RUFORUM), under the umbrella of the African Union Comprehensive African Agricultural Development Program. (CAADP). The study is structured as follows: section two describes the role of higher agricultural education in the wider agro-innovation system and the means through which higher education can drive transformation of the agri-food sector and economic development in Africa; section three describes global trends in agriculture that will drive changes in employers’ knowledge and skills needs; section four describes the implications of these trends for skill and knowledge needs; section five describes the core challenges that universities face in transforming to be more responsive to needs; and the final section six provides recommendations on reforms and investments to strengthen higher education in Africa.